PWE-025 Serum Calprotectin – A Novel Diagnostic and Prognostic Marker in Inflammatory Bowel Diseases. (17th August 2016) - Kalla, R; Kennedy, NA; Ventham, NT; Boyapati, R; Adams, AT; Nimmo, E; Visconti, M; Drummond, H; Ho, GT; Pattenden, R; Wilson, DC; Satsangi, J
Abstract : Introduction: There is an unmet need for novel blood based biomarkers that offer timely and accurate diagnostic and prognostic testing in Inflammatory Bowel Diseases (IBD). We aimed to investigate the diagnostic and prognostic utility of serum calprotectin (SC) in IBD Methods: A total of 156 patients (82 IBD and 74 non-IBD) were sampled within 90 days from diagnosis (median 0 days; IQR 0–7). A multibiomarker diagnostic and prognostic model was derived using multivariable logistic regression analysis. Treatment escalation was defined as the need for escalation and establishment of 2 or more immunomodulatory therapies and/or surgery for disease flare after initial induction of disease remission (criteria previously used by Lee et al) (1). Cox proportional hazards model was derived to assess the contribution of each variable to disease outcomes Results: SC correlated strongly with current biomarkers including CRP (rho = 0.60, p = 1.4x10 −16 ) faecal calprotectin (FC) (rho = 0.51, p = 1.6x10 −4 ). Paired FC was available within 30 days (median 0 days, IQR: -4 to5 days) of SC in 50 patients (IBD n = 30, non-IBD n = 20).The area under receiver operating characteristic discriminating IBD from controls was similar for FC and SC(0.95, 95% CI 0.87–1.00 and 0.89, 95%CI 0.81–0.98 respectively;p = 0.36). SC was the strongest individual predictor of IBD diagnosis (odds ratio (OR): 12.33 (95% CI 4.48–38.33, p = 3.5×10 −6 ) compared with other markers (CRP: OR 4.44, CI 1.58–12.90; albumin: OR 5.65, CI 1.98–17.16). At follow up (median 342 days; IQR: 88–563), a total of 1 (2%), 16 (47%), 23 (51%) patients required treatment escalation in the IBDU, CD and UC group respectively.SC predicted treatment escalation and/or surgery in IBD (HR 2.4, 95% CI: 1.1–4.9), in particular CD (HR 4.1, 95% CI 1.1–14.7). A model incorporating SC, CRP and albumin has a positive likelihood ratio of 20.03 for IBD.At 1 year, our prognostic model can predict treatment escalation in IBD in 65% of cases (95% CI: 43–79%) and 80% (95% CI: 31–94%) in CD if 2 or more blood marker criteria are met. Conclusion: Sampling faeces can be a hurdle for patients and some individuals can decline FC testing. These factors impact on the practical utility of FC.SC shows promise as a diagnostic and prognostic biomarker in IBD. Our findings warrant further exploration and validation within large multicentre cohorts. Reference: 1 Lee JC, et al . Gene expression profiling of CD8+ T cells predicts prognosis in patients with Crohn disease and ulcerative colitis. J Clin Invest 2011;121 :4170–9. Disclosure of Interest: None Declared